Teacher training for Inclusive Classroom: A Road Map - Sarwer, Ghulam (IJRDO- Journal of Educational Research, 2016)
This paper presents the current status of teacher education for inclusive education, i.e. preparation of teachers for inclusive classroom as well as the need for introducing changes in the inclusive education curricula, leading towards a more efficient development of competences for working with all students. It is found that the inclusive education curricula do not contribute to the development of competences and preparation of teachers for inclusive classroom. The basic obstacles in preparation of teacher for inclusive education include inadequate curricula, dysfunctional professional practices and negative attitude of educators towards inclusive education. The concluding part of this paper points out that the key factors for changes in inclusive education comprise sufficient motivation of educators, awareness about the responsibility of the faculty to teach in accordance with the inclusive education concept, as well as the support to these faculties through wide social action. The implications for enhancement of training programme for teachers include introducing changes into study programmes and implementing the strategies in practice, leading towards more effective preparation of teachers for inclusive classroom